Soft tissue management at delayed implant loading in the aesthetic zone: A case report - Prokić Aleksandra; Miličić-Lazić Minja; Đorđević Igor (Serbian Medical Society - Dental Section, Belgrade, 2023)
Emergence profile of implant-supported crowns is defined by the characteristics of supracrestal connective tissue (SCT), located between the implant platform and cervical soft tissue margin. This paper reflects the soft tissue contour management of implant-supported screw-retained crowns and the transfer of emergence profile using an indirectly customized impression coping. A 27-year-old male was referred for endosseus implant placement (Straumann BLT 0 4.1 mm × 12 mm) in a region of a maxillary right central and lateral incisor. Teeth were extracted due to a cystic formation in the mentioned region. Following the delayed implant loading protocol, implants were exposed, and provisional crowns were fabricated to support marginal mucosa and papillae and to mimic the contralateral site. During the three months of temporization, three-dimensional peri-implant soft tissue changes were validated, and temporary crowns were re-contoured every two weeks to obtain dynamic compression. When adequate soft tissue architecture was achieved, the impression for definitive crowns was taken using customized transfer technique to be able to register the emergence profile of provisional crowns. This case report described a soft tissue management technique, where remodeling the provisional restoration allowed soft tissue to be reshaped. Individual transfer impression technique provides an accurately captured emergence profile of the soft tissue contours around implants in the aesthetic zone. This technique enables contouring of the transmucosal part of the definitive restoration according to the results obtained by individual dynamic compression, which leads to healthy soft tissue contours as well as satisfactory aesthetic results.